Knowledge workplaces - Alexander, Keith (Facilities ;, 2004)
Social work space is emerging as a major avenue for sharing knowledge and the creation of social capital. Social space and physical space needs to be in balance. Virtual space must also be included in this mix. The physical work environment can support the new sense of place and space in the knowledge work. This paper discusses how to use tangible assets to make intangible social space perform better. In this paper the problemis approached by analysing the balance between physical, social and virtual space. The method used is based on "type" analysis, which uses the structure of a fourquadrant.